Double-Diffusive MHD Viscous Fluid Flow in a Porous Medium in the Presence of Cattaneo-Christov Theories - Bidemi Olumide Falodun; Adeola John Omowaye; Funmilayo Helen Oyelami; Homan Emadifar; Ahmed A. Hamoud; S. M. Atif (Modelling and Simulation in Engineering)
The Cattaneo-Christov model will be used to examine the significance of heat generation, viscous dissipation, and thermal radiation on a double-diffusive MHD flow in this study. In this study, it was discovered that heat and mass transfer can be affected by nonlinear buoyancy significance. The flow direction was subjected to a uniform magnetic field. A set of partial differential equations governs the current design (PDEs). In order to simplify these equations, they are converted into ordinary differential equations (ODEs). In order to numerically solve the nonlinear ODEs, the spectral relaxation method (SRM) is utilized. In order to decouple and linearize the equation sets, the SRM employs the Gauss-Seidel relaxation method. Geothermal power generation and underground storage systems are just a few examples where this research could be put to use. When compared to previous findings, the current outcomes were discovered to be closely related. Owing to an increase in Lorentz force, the imposed magnetic field slows down fluid motion. Viscosity dissipation and heat generation all contribute to the formation of an ever-thicker thermal boundary layer. When the Cattaneo-Christov models are used, the thermal and concentration boundary layers get a lot thicker.